The Influence of Job Description and Jobplacementon Job Satisfaction of Employees of PT. Deli Kencana Palace Medan - Ronauli Fransiska Pasaribu; Rahmat Hidayat Harahap (Jurnal Mantik, 2022)
PT ISTANA DELI KENCANA Medan or better known as PT ISTANA DELI KENCANA  Medan, is one of the leading providers of freight forwarding services in Medan. PT ISTANA DELI KENCANA  Medan is one of the branch offices of PT ISTANA DELI KENCANA   Medan. Employee job satisfaction is still low because there are still many employees who are often late. The job descriptions of employees that are formed are not good because it is still unclear about the duties and responsibilities of each employee so that employees cannot work optimally. Employee work placement is not good because it is not in accordance with the ability of employees so that employees cannot work optimally. This research uses quantitative descriptive research. The total population in the study was 34 employees with a sampling technique using a saturated sample.Simultaneously there is a significant influence between the variable job description and job placement on job satisfaction of employees of PT ISTANA DELI KENCANA   Medan. While partially found job description variables have a significant effect on job satisfaction of employees of PT ISTANA DELI KENCANA   Medan. Partially, it was found that the job placement variable had a significant effect on job satisfaction of PT ISTANA DELI KENCANA   Medan. The results of this study indicate that the variable job placement has more influence than job descriptions on job satisfaction of employees of PT ISTANA DELI KENCANA Medan.